The multiple sclerosis risk allele within the AHI1 gene is associated with relapses in children and adults - Graves, J; Barcellos, L; Simpson, S; Belman, A; Lin, R; Taylor, B; Ponsonby, A; Dwyer, T; Krupp, L; Waubant, E; van der Mei, I (Elsevier, 2017)
Background While common variant non-HLA (human leukocyte antigen) alleles have been associated with MS risk, their role in disease course is less clear. We sought to determine whether established multiple sclerosis (MS) genetic susceptibility factors are associated with relapse rate in children and an independent cohort of adults with MS. Methods Genotyping was performed for 182 children with MS or clinically isolated syndrome with high risk for MS from two Pediatric MS Centers. They were prospectively followed for relapses. Fifty-two non-HLA MS susceptibility single nucleotide polymorphisms (SNPs) were evaluated for association with relapse rate. Cox regression models were adjusted for sex, genetic ancestry, disease-modifying therapy (DMT), 25-OH vitamin D level and HLA-DRB1*15:01/03 status. Investigation of pediatric subject SNP results was performed using a second cohort of 141 adult MS subjects of Northern European ancestry from the Southern Tasmanian Multiple Sclerosis Longitudinal Study. Results For pediatric subjects, 408 relapses were captured over 622 patient-years of follow-up. Four non-HLA risk SNPs (rs11154801, rs650258, rs12212193, rs2303759) were associated with relapses (p<0.01) in the pediatric subjects. After adjustment for genetic ancestry, sex, age, vitamin D level, DMT use and HLA-DRB1*15 status, having two copies of the MS risk allele within AHI1 (rs11154801) was associated with increased relapses among children (HR = 1.75,95%CI = 1.18–2.48, p = 0.006) and this result was also observed among adults (HR = 1.81,95%CI = 1.05–3.03, p = 0.026). Conclusions Our results suggest that the MS genetic risk variant within the gene AHI1 may contribute to disease course in addition to disease susceptibility.